Cotransplantation of Olfactory Ensheathing Cells and Schwann Cells Combined with Treadmill Training Promotes Functional Recovery in Rats with Contused Spinal Cords. Issue 1 (January 2013) - Sun, Tiansheng; Ye, Chaoqun; Zhang, Zhicheng; Wu, Jun; Huang, Hongyun
The present study investigated the ability of cotransplantation of Schwann cells (SCs) and olfactory ensheathing cells (OECs) combined with treadmill training in facilitating neuronal plasticity and promoting hindlimb function recovery of subacute moderate thoracic (T10) spinal cord contusion in rats. Two weeks postinjury, SCs were injected directly into the lesion, while OECs were injected into the adjacent tissues. The treadmill training with the rats began postinjury on day 7, with each session lasting 20 ± 10 min per day, 5 days per week, for 10 weeks. At the 11th week postinjury, OECs were found migrating longitudinally and laterally from the injection site to the injury site through the gray and white matter, while some traveled along the central canal or pia. The SCs remained densely packed and concentrated at the transplant site. The transplanted SCs supported ingrowth of numerous, densely populated neurofilament-positive (NF + ), MBP + axons. The OECs promoted elongation of moderate NF +, GAP-43 + axons and a few MBP + axons in parallel with OEC processes. The GFAP immunoreactivity in the spared tissue surrounding the graft of SCs and OECs at the lesion site was less intense than that in the DMEM group. Treadmill training had no effect on GFAP immunoreactivity. Treadmill training increased the number of TH-immunoreactive neurons in the gray matter of L2 spinal cord. Moreover, cotransplantation of OECs and SCs significantly increased the BBB score during 5–8 weeks postinjury alongside treadmill training between 5 and 11 weeks. Cotransplantation of OECs and SCs combined with treadmill training resulted in the highest BBB score at 4 and 11 weeks. The study details the differential mechanisms of neuronal plasticity: (1 ) axon growth and remyelination induced by cotransplantation of OECs and SCs and (2 ) neuron plasticity below the lesion enhanced by treadmill training. The synergistic effects of the combined strategy enhance functional recovery. This manuscript is published as part of the International Association of Neurorestoratology (IANR) supplement issue of Cell Transplantation .